ANALISIS STRATEGI IMPLEMENTASI CORPORATE CULTURE BANK SUMUT CABANG SYARIAH SIBOLGA PADA MASA PANDEMI COVID-19 DALAM PERSPEKTIF ISLAM - Ummi Kalsum; Muhammad Ramadhan; Nurul Jannah (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
In general, Corporate Culture is an opportunity to expand or form human resources with changes in attitudes and behavior such as beliefs, values, and norms that characterize the company which is followed by company members and is expected to align themselves with emerging and future obstacles. At Bank Sumut, the Sibolga Syariah Branch, there is a corporate culture with the BEST corporate values, vision, mission, and company motto based on an Islamic perspective. However, during this COVID-19 pandemic, there are several company values ​​that are less effective in their implementation as usual, namely Energetic, Friendly, High Integrity, and Safe. This study aims to identify the principles of corporate culture, corporate culture in an Islamic perspective, and strategies for implementing corporate culture during the COVID-19 pandemic at Bank Sumut Syariah Branch Sibolga. In this study, the researcher used a descriptive qualitative study technique. Data collection methods are using observation, interviews, and documentation. The results of the study conclude that the principle of corporate culture at Bank Sumut Syariah Branch Sibolga Sibolga is the first company values ​​which are abbreviated as BEST, vision, mission, and company motto. Second, the corporate culture at Bank Sumut Syariah Branch Sibolga is based on an Islamic perspective. Third, to overcome problems with several company values ​​that experienced obstacles during the covid-19 pandemic, the company made a design for the application of Bank Sumut Syariah Sibolga corporate culture during the covid-19 pandemic